Integrasi Kecerdasan Buatan dalam Pembelajaran Digital Multimodal dan Adaptif: Sebuah Systematic Literature Review - Reski Reski; Husnul Khotimah; Muhammad Alfian Solo; Abdul Hakim; Nurhikmah H; Safaruddin Safaruddin (SAP (Susunan Artikel Pendidikan), 2025)
The development of Artificial Intelligence (AI) has made a significant contribution to innovations in digital learning. This study aims to analyze how AI is utilized to support the development of multimodal learning resources, interactive animations, and adaptive learning experiences for students. The method used is a Systematic Literature Review (SLR) based on the PRISMA 2020 guidelines. Data were collected from the Scopus database using a Boolean query that combined the keywords “AI” and “educational animation” for the years 2020–2025. Out of 166 articles found, only 11 met the inclusion criteria and were thematically analyzed. The results show that AI plays a crucial role in enriching digital learning strategies. Generative AI supports the creation of multimodal learning resources, deep learning promotes the development of interactive educational animations, and adaptive AI systems enable learning experiences responsive to individual student abilities. In conclusion, the application of AI enhances the effectiveness, interactivity, and personalization of digital learning, contributing to the formation of an innovative and learner-centered educational ecosystem.